1997
DOI: 10.1074/jbc.272.35.22053
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Osteoclast Bone Resorption by Interstitial Collagenase

Abstract: Osteoclasts form an acidic compartment at their attachment site in which bone demineralization and matrix degradation occur. Although both the cysteine proteinases and neutral collagenases participate in bone resorption, their roles have remained unclear. Here we show that interstitial collagenase has an essential role in initiating bone resorption, distinct from that of the cysteine proteinases. Treatment of osteoclasts with cysteine proteinase inhibitors did not affect the number of resorption lacunae ("pits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
169
1
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(174 citation statements)
references
References 44 publications
(48 reference statements)
3
169
1
1
Order By: Relevance
“…8,10 Moreover, collagen fragments generated by MMP activity might attract and activate osteoclasts. 35 Another important role of MMPs in the reversal phase 34 of bone remodeling has been stipulated by Everts et al, 9 who demonstrated removal of bone collagen left by osteoclasts in Howship's lacunae by bone lining cells producing MMPs. This process is followed by formation of new bone by osteoblasts.…”
Section: -32mentioning
confidence: 99%
“…8,10 Moreover, collagen fragments generated by MMP activity might attract and activate osteoclasts. 35 Another important role of MMPs in the reversal phase 34 of bone remodeling has been stipulated by Everts et al, 9 who demonstrated removal of bone collagen left by osteoclasts in Howship's lacunae by bone lining cells producing MMPs. This process is followed by formation of new bone by osteoblasts.…”
Section: -32mentioning
confidence: 99%
“…In osteoclasts, cells that are essential for bone remodeling, densely packed V-ATPases reside in a specialized domain of the apical plasma membrane known as the ruffled membrane, where they acidify an extracellular compartment at the site of attachment to bone (5). Osteoclast proton secretion is required both for dissolution of bone mineral and for efficient degradation of bone matrix proteins by acid cysteine proteinases (6).…”
Section: Vacuolar Hmentioning
confidence: 99%
“…Whereas several proteases are implicated in this process, it becomes increasingly clear that MMPs play an essential role. MMPs can function as coupling factors, allowing osteoblasts to initiate bone resorption by generating collagen fragments that activate osteoclasts (Holliday et al 1997). Degradation of the osteoid layer by MMPs is a necessary process before osteolysis can occur because the osteoid layer hinders osteoclasts from adhering to bone.…”
Section: Discussionmentioning
confidence: 99%